Regulating with market information - BUSTOS, Francisco Javier Contreras (2023)
Governments often provide goods and services by hiring private firms that are already operating in the market. This is the case of the Programa Universidade para Todos(PROUNI), created in 2004 to provide scholarships to low-income students by private institutions of higher education. In exchange, the private institutions participating in the program benefit from tax exemptions. Studies have shown a positive impact of PROUNI on variables such as accessibility, permanence and academic performance. However, studies conducted by the Federal Court of Auditors have demonstrated that the government is paying a higher price than the market median. Traditional theory treats regulated firms as if they exclusively serve the regulator. In reality, firms usually operate in the market. These market operations can provide information for the regulator. This study examines how the regulator can use market information to save information rents and reduce allocative distortions. Assuming that costs are not observed by the government, we follow the theoretical framework implemented by Baron and Myerson, who analyze contracts based on the principal-agent paradigm. The innovation to the regulatory literature is that it uses the firm’s own information in the market to reveal its type. Using a model with one monopolistic firm and another with two firms in an oligopolistic market, interesting results are obtained: when the government observes what the firm does in the private market and conditions its behavior on it, optimal regulation requires the quantity of the first-best for the efficient firm and less distortion for the inefficient firm’s contract. In addition, the use of this information allows for fiscal savings.